A proximate remove: queering intimacy and loss in The tale of Genji - Jackson, Reginald R. (University of California Press, 2021)
"How might queer theory transform our interpretations of medieval Japanese literature and how might this literature reorient the assumptions, priorities, and critical practices of queer theory? Through close readings of The Tale of Genji, an eleventh century text that depicts the lifestyles of aristocrats during the Heian period, A Proximate Remove explores this question by mapping the destabilizing aesthetic, affective, and phenomenological dimensions of experiencing intimacy and loss. The spatiotemporal fissures Reginald Jackson calls 'proximate removes' suspend belief in prevailing structures. Beyond issues of sexuality, A Proximate Remove contends that Genji queers in its reluctance to romanticize or reproduce a flawed social order. This hesitation enhances how we engage premodern texts and question contemporary disciplinary stances"--